2018
DOI: 10.1002/prp2.388
|View full text |Cite
|
Sign up to set email alerts
|

RNA expression profiling in sulfamethoxazole‐treated patients with a range of in vitro lymphocyte cytotoxicity phenotypes

Abstract: The lymphocyte toxicity assay (LTA) is a proposed surrogate marker of sulfonamide antibiotic hypersensitivity. In the LTA, peripheral blood mononuclear cells (PBMCs) undergo apoptosis more readily in hypersensitive versus tolerant patients when exposed to drug‐hydroxylamine metabolites in vitro. The purpose of this study was to identify key gene transcripts associated with increased cytotoxicity from sulfamethoxazole‐hydroxylamine in human PBMCs in the LTA. The LTA was performed on PBMCs of 10 patients hyperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…TMEM176B inhibits NLRP3 inflammasome activation to regulate adaptive and innate antitumor responses, suggesting that TMEM176 may be a potential immunotherapy target for pancreatic cancer ( 47 ). Additionally, numerous studies have shown that TMEM123 and TMEM66 in T cells, and TMEM208, TMEM59, and TMEM258 in B cells, are closely related to inflammatory response and participate in tumor immune response, which is consistent with our findings ( 48 50 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TMEM176B inhibits NLRP3 inflammasome activation to regulate adaptive and innate antitumor responses, suggesting that TMEM176 may be a potential immunotherapy target for pancreatic cancer ( 47 ). Additionally, numerous studies have shown that TMEM123 and TMEM66 in T cells, and TMEM208, TMEM59, and TMEM258 in B cells, are closely related to inflammatory response and participate in tumor immune response, which is consistent with our findings ( 48 50 ).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, numerous studies have shown that TMEM123 and TMEM66 in T cells, and TMEM208, TMEM59, and TMEM258 in B cells, are closely related to inflammatory response and participate in tumor immune response, which is consistent with our findings (48)(49)(50).…”
Section: Discussionsupporting
confidence: 92%
“…In rhabdomyosarcoma (RMS), miR-7 showed the anti-tumor effect to induce necroptosis by targeting mitochondrial proteins SLC25A37 and TIMM50 [ 32 ]. SLC25A37 was significantly over-expressed in high cytotoxicity patients [ 33 ] and loss of TIM50 suppressed tumor cell growth and induced apoptosis in breast cancer [ 34 ] and loss of TIM50 suppressed tumor cell growth and induced apoptosis in breast cancer [ 35 ]. Several miRNAs were reported to regulate necroptosis by targeting and regulating RIP-1.…”
Section: Necroptosis and Cancer Metastasismentioning
confidence: 99%
“…In rhabdomyosarcoma (RMS), miR-7 exerts an anti-tumor effect by targeting mitochondrial proteins SLC25A37 and TIMM50, ultimately inducing necrosis 35 . Moreover, SLC25A37 is significantly overexpressed in patients with high cytotoxicity 36 , while TIM50 deficiency suppresses tumor cell growth and induces apoptosis in breast cancer 37 . Based on the findings of these previous investigations, the two miRNAs identified in our study, which markedly impact the survival of UCEC patients, are also closely associated with prognosis in other malignancies.…”
Section: Discussionmentioning
confidence: 99%